komerebi: (n.) sunlight that filters through the leaves of trees. - Tran, Cynthia (Stimulus: A Medical Humanities Journal, 2023)
The following photographs were taken at a Buddhist temple located in central Houston, Texas. Since early times, Buddhism has held a history of medicinal practices, focusing on natural and spiritual care, rather than using harsh chemicals and modern technology. Since ancient times, disease concerns within the religion of Buddhism require care in all aspects of a human's life, including natural, mental, physical, environmental, and societal. Complete harmonization of these aspects will then cure the patient. These aspects can also be taught to the daily physician, which lays the groundwork for those who follow, morals and ethics. Health, in and of itself, is to be understood as a whole. The relationship in which an individual connects not only with the body and mind, but the social relationships around them, and the environment in which one submerges themselves. Both physician and patient must understand to be absolute. The idea behind these photos does not lie in what the individual sees, but in the beauty and serenity of the environment and how one can be environmentally aware of the surroundings and harmony that nature has given us. When I was editing these photos, I noticed how calm and quiet the environment was, and how each piece of nature coincided with one others. These film-like qualities date back to nostalgic times and showcase each photo in its glory, through saturation and balance. When deciding on a title for this project, I decided to go with something of Japanese origin, since medicinal practices and holistic care of people seem to be the most respected among all cultures. Japan also has a rich community with Buddhist followers, which I also considered after doing extensive research. As a future physician, I want to be able to focus on being at one with myself, whether that be through my beliefs, or through my work, as those qualities become important later on in life. I also invite those who view this project to try and find ways to be at peace with themselves, whether that be to connect with nature or practice mindfulness through meditation. You can find more of my works through my Instagram handle @cybdy.captures . I hope you enjoyed viewing this capture set and finding some peace within yourself.